Tyranny of Conventions: A Comparative Study of Blake's Visions and Hardy's Tess - Roohollah Datli Beigi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2019)
William Blake's Visions of the Daughters of Albion (1793) and Thomas Hardy's Tess of the d'Urbervilles (1891) have much in common. Both deal with female sexuality and question the society's sexual and religious mores by portraying a revolutionary woman who fights to gain her autonomy and self-assertion. However, as subjects/products of the dominant ideologies and conventions of their time, Blake and Hardy seem to empower the very conventions they try to reject in portraying heroines tyrannically destroyed by the long-held conventions that condemn an unmarried woman's sexual experience. These heroines' self-assertion/rebellion fails tragically. In this paper we argue that, comparatively, the ambivalent treatment of the notion of independent woman is the most significant common feature in Blake's poem and Hardy's novel. On the one hand, both Blake and Hardy introduce a woman with a new sexual identity and, on the other hand, they deprive their heroines of voice and independence.